Development of aqueous magnesium–air batteries: From structure to materials - Liu, Hongxuan; Zhang, Ting–an (Journal of alloys and compounds, 2024)
With the development of carbon neutrality strategies, highly polluting and non–renewable fossil fuels are gradually being replaced by electrochemical energy storage systems. Therefore, developing high–performance, safe, and green electrochemical energy storage systems has become a research hotspot. Metal–air batteries are a new type of energy storage system with good discharge performance and economic benefits. Magnesium is an energy–storage metal with abundant reserves and low pollution. Its light weight and excellent electrochemical properties make it a key material for energy storage research. Magnesium–air batteries combine the advantages of magnesium and metal–air batteries, with higher energy density, stable discharge, no charging, direct mechanical replacement, and no environmental pollution, highlighting their potential as. Promising energy storage systems. This article reviews the structure and principles of water–based magnesium–air batteries, summarises and compares the optimisation methods for different anodes and cathodes, introduces the development and advantages of magnesium seawater batteries, and discusses the prospects for magnesium–air batteries. Aiming to help researchers understand the current research progress of water–based magnesium–air batteries, discover new research directions based on a comparison of different optimisation methods, and promote the development of magnesium–air battery research, which has important implications for basic research on magnesium–air batteries. [Display omitted]